Collusion or Illusion : a Tri-State Analysis of Gas Prices - Possi, Ben; Anderson, Emily (My University, 2013)
The purpose of this study was: 1. to identify locational factors and market conditions that could explain Eau Claire's purportedly high and uniform retail gas prices; and 2. to access the impact of Wisconsin's "Minimum Markup Law" on price dispersion.
Color poster with text, maps, tables, charts, and graphs.
Keywords: Gas prices--Wisconsin--Eau Claire; Minimum markup law--Wisconsin; Unfair Sales Act--Wisconsin; Posters